A 5 year retrospective study on epidemiological pattern of ocular trauma - Manhas, Angli; Manhas, Rameshwar S.; Manhas, Gaurav S.; Sharma, Rishabh; Gupta, Dinesh (International Journal of Research in Medical Sciences, 2019)
Background: One of the delicate structure in the human body is eye and trauma to the eye is essentially a very grave matter. Major cause of preventable monocular blindness and visual impairment in the world is ocular trauma. So any injury to the eye must be deemed to be an ocular emergency and should be handled with utmost care. Despite its public health importance, there is relatively less population based data on the magnitude and risk factors for ocular trauma specially from developing countries. The objective of the study was to find out the epidemiological pattern of ocular trauma. Methods: The present study was 5 year retrospective study of all the patients who reported directly with ocular injury or referred from the casualty to the department of ophthalmology from January 2013 to January 2018. Various parameters like age, sex, mode of injury, type of injury etc. of all patients seen during this period were analyzed. Results: Total of 4192 ocular trauma patients were seen during study period. Maximum number of ocular trauma patients i.e. 1146 were seen in age group of 21-30 years. Males i.e. 3490 outnumbered females in the present study. Road traffic accidents were the most common cause of ocular trauma and accounts for 1760 cases. Most common reported ocular trauma was periorbital oedema/ecchymosis followed by laceration. Surgical intervention was done in 1660 cases whereas 2532 were managed medically. Conclusions: From present study, we may conclude that the maximum number of ocular trauma patients were seen in the age group of 21-30 years with more preponderance in males. Road traffic accidents were the most common cause of ocular trauma. The fact that the lifetime prevalence of ocular trauma is higher than that of eye diseases, which can be decreased by implementing the traffic rules with strict force and imposing heavy fine and license cancellation for drunken driving.